Advances in cold atom UHV/XHV metrology. (January 2023) - Wu, Xiangmin; Cheng, Yongjun; Dong, Meng; Sun, Wenjun; Zhang, Suzhao; Ma, Zhuoya; Li, Yanpeng; Jia, Wenjie; Feng, Tianyou; Wu, Chengyao
Abstract: Cold atom vacuum metrology is a technique for linking science and applications of cold atom and vacuum sensing based on a fundamental atomic property, the collision cross-section. It is expected to establish a quantum ultra-high/extreme-high vacuum primary standard. This paper summarises and analyses in detail the research advances of the technique. It focuses on the design and optimization of experimental apparatus in the cold atom capture process and the measurement of critical parameters during the observation process for the lifetime of cold atoms. In addition, the comparison between standards is presented to verify the performance of the new standard. It concludes with an outlook on the breakthrough points and development directions of the technique for practical applications. Highlights: The designs and improvements of the cold atom apparatus units to meet the vacuum measurement requirements are analysed. The determinations of critical parameters for the cold atom vacuum measurement in different atomic traps are reviewed. Further research directions for cold atom vacuum metrology towards practical applications are proposed.